Pengaruh Kinerja Maqashid Syariah dan Islamic Social Reporting terhadap Agresivitas Pajak dengan Ukuran Perusahaan sebagai Variabel Moderasi (Studi Empiris Pada Perbankan Syariah di Indonesia Tahun 2016-2020) - Taufikurohman, Rizki; Ekawati, Evi; Devi, Yulistia (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2022)
Purpose: This study aims to determine whether there is a effect of maqashid sharia performance and islamic social reporting on tax aggressiveness with company size as a moderating variabel. Research Methodology: This research is a quantitative research using secondary data in the form of annual report of islamic banking in Indonesia period 2016 to 2020 registed in OJK. The technique samples were conducted with purposive sampling to obtain 45 samples used in this study. Data analysis methods Moderated Regression Analysis (MRA) by using tools SPSS Statistics 26.0. Results: The results showed that the variable performance maqashid sharia does not effect on tax aggressiveness, while islamic social reporting has a positive effect on tax aggressiveness. The results of Moderatd Regression Analysis showed that the size of the company is able to moderate the influence of performance maqashid sharia on tax aggressiveness. But the size companies unable to moderate the influence islamic social reporting on tax aggressiveness. Limitations: The use of independent variables only uses sharia maqashid performance and Islamic social reporting, it is hoped that further research can add other variables that have not been included in this study. In addition, the measurement of tax aggressiveness in this study uses ETR (effective tax rate), it is hoped that in future studies using other measurements such as Cash Effective Tax Rate (CETR) or Book Tax Difference (BTD). Contribution: This research can be a reference for further researchers related to tax aggressiveness. In addition, for investors, it is better for investors in making decisions to first examine how the performance of a company and still comply with tax avoidance is not a natural thing but it is always done and will have a good impact on both parties concerned, both from the investor, company and government.